Pengaruh Penggunaan Media Quizizz Terhadap Hasil Belajar Siswa Tentang Sifat-Sifat Benda Di Kelas V SD - Musfirah Musfirah; Nana Alfiana; Shasliani Shasliani (Jurnal Pendidikan dan Pembelajaran Sekolah Dasar (JPPSD), 2022)
This study aims to determine the effect of using quizizz learning media on student learning outcomes about the properties of objects in class V UPTD SDN 1 Barru. This research approach is quantitative with experimental research type and Pre-Experimental design in the form of One Group Pretest-Posttest Design. The results of descriptive statistical analysis show that the average value of learning outcomes using the quizizz media is increasing. The results of inferential statistical analysis by testing the hypothesis using the paired sample t-test showed Sig (2-tailed) < 0.005 (0.000 < 0.05) indicating that the significance value of 0.000 was smaller than = 0.05,H0 thus was rejected. and Ha accepted. Based on these data, it can be concluded that the use of quizizz media affects student learning outcomes about the properties of objects in class V UPTD SDN 1 Barru.